Application of seismic attribute and spectral decomposition: Example of fluvial system during miocene in field a, Malay basin - Malik, M.H.A. (2019)
Stratigraphic channels in field A Malay Basin including those with reservoir potential have been defined seismically. There were two exploration wells in field a however, the wells were abandoned due to low structural relief and volume were below economic criteria. This study discusses how seismic attribute and spectral decomposition give geomorphological information in different stratigraphic levels of Miocene age at Top F, H, I, Group I-50 and I-60. Facies analysis, seismic attribute, spectral decomposition and colour blending were implemented to identify hydrocarbon potential in stratigraphic traps and to enhance seismic resolution. Channel anomalies can be identified in seismic reflections characterized by high-amplitude events with chaotic reflections. Numerous sub-parallel reflection with high amplitude is observed in the upper formation. Several seismic attributes were used from the 3D seismic dataset to identify the geomorphologic features, potential reservoir variations, besides distribution and to extract the anomalies. Physical attributes which are related to amplitude, frequency, phase and their derivative were used including variance, instantaneous frequency, sweetness and spectral decomposition. Sweetness is the combination of lateral continuity and reflection strength. High reflection strength indicates maximum amplitude of the largest peak or through of real trace. This is especially, true when an event is a composite reflection. Amplitude attribute provides better spatial definition of events and bright spots could be enhanced. Instantaneous frequency shows composite frequency of the individual reflections contributing to a particular reflector. This composite is a useful correlation tool. Rapid changes in frequency are sometimes indicator of pinchouts such as oil/gas and water contacts. Low frequency anomalies are observed in zones below hydrocarbon reservoirs. Meanwhile, instantaneous phase is useful in stratigraphic analysis of certain sections because the sharp zero crossings that results may emphasize lateral discontinuities, pinchouts and angularities. The combination of attribute analysis and spectral decomposition aids the interpretation and identification of some channel patterns and channel distribution. Two methods of spectral decomposition are used Short Time Fourier Transform (STFT) and S-transform which focus on spatial and temporal range, respectively. Red Green Blue (RGB) colour blending represents different frequency ranges of low, mid and high frequency bands and display as a single image. This method reveals additional information such as depositional elements, anomaly identification, bed thickness, presence of fluids and help to resolve petrophysical heterogeneity. This study reveals that there are strong evidences of hydrocarbon potential in stratigraphic traps for further exploration within the study area. Â© Medwell Journals, 2019.